Prediction of diabetes induced complications using different machine learning algorithms - Rahman, Tahsinur; Farzana, Sheikh Mastura; Khanom, Aniqa Zaida (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.